Problems and Collisions of Vaccinology - E. P. Kharchenko (Эпидемиология и вакцинопрофилактика, 2024)
The article discusses the limitations of the protective potential of the immune system associated with the peculiarities of the evolutionary mechanisms of the emergence of protein diversity and the late emergence in the evolution of the adaptive immune system, as well as problems associated with the formation of immunity to viral infections and immune collisions during vaccination. Using the example of hemagglutinin of the H1N1 influenza virus and S protein of the SARS-Cov-2 coronavirus, the features of the amino acid composition of their immunodominant (NA1 and S1) and subdominant (NA2 and S2) subunits are illustrated and the possibility of creating a universal vaccine against influenza viruses is analyzed. The principle of a new method for detecting linear peptide immunoepitopes recognized by MHC I and II and biomarkers of long-term immunity in surface viral proteins used as vaccines is described. The model of proteolysis of vaccine proteins in immunoprotesomes and lysosomes, features of the amino acid composition of surface proteins of viruses to which vaccines cause long-term immunity, and viruses to which vaccines have not yet been developed, as well as possible collisions with mRNA vaccines are examined. Possible collisions with mRNA vaccines are also being considered in connection with the identification of gene encoding limitations.